Application of Baro-Altimeter Sensor in Emergency Positioning and Navigation Based on Compass GEO Satellites. (29th September 2013) - Zhan, Jianwei; Pang, Jing; Zhang, Guozhu; Ou, Gang
Abstract : Frame synchronization time of geostationary Earth orbit (GEO) satellites is faster than that of incline geosynchronous satellite orbit and medium Earth orbit satellites in Beidou navigation satellite system (BDS). So time to first fix can be reduced greatly with GEO satellites (GEOs) to provide emergency positioning service during the cold start process. Meanwhile, GEOs can also be utilized to provide radio determination satellite services. Therefore, it is meaningful to research the emergency positioning algorithm based on GEOs. However, due to the poor geometry of the GEOs, the availability and accuracy degrade distinctly. To solve this problem, a low-cost high resolution MS5534B barometric (baro-) module is applied to BDS. Firstly, the principle of emergency positioning based on a baro-altimeter sensor and its performance such as the accuracy are elaborated. Then the effects of baro-altimeter sensor measurement error on positioning are analyzed. Finally, after analyzing the limitation of the conventional algorithms, a new high-accuracy emergency positioning algorithm with baro-altimeter sensor aiding is proposed, which is not limited by the integration and user's altitude. In comparison to the conventional algorithms, the stimulant and experimental results validate the effectiveness, robustness, and higher performance of the proposed algorithms incorporated with sensors.